Antimicrobial Activity of Black Mustard Seed (Brassica nigra L.) - TURAN AKKOYUN, H.; DOSTBIL, NURSEL; KIRAN, EZLEM (Asian Journal of Chemistry, 2010)
This study was made to determine the antimicrobial activity of mustard (Brassica nigra L.). For this purpose extract of mustard which was prepared in diethyl ether tested on test strains of P. aeruginosa ATCC 25853, E. coli ATCC 11239, K. pneumoniae FML 5, M. luteus ATCC 9345, E. faecalis ATCC 29212, B. megaterium DSM 32 and S. aureus ATCC 25923 with disk diffusion method as in vitro. The present investigation shows the different levels of inhibitory activity to test strains while the mustard has inhibitory activity on the all test strains.